2020
DOI: 10.1128/cmr.00053-19
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Application of 16S rRNA Gene Cycle Sequencing for Routine Identification of Bacteria in the Clinical Microbiology Laboratory

Abstract: SUMMARY This review provides a state-of-the-art description of the performance of Sanger cycle sequencing of the 16S rRNA gene for routine identification of bacteria in the clinical microbiology laboratory. A detailed description of the technology and current methodology is outlined with a major focus on proper data analyses and interpretation of sequences. The remainder of the article is focused on a comprehensive evaluation of the application of this method for identification of bacterial pathogens based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 586 publications
2
122
0
2
Order By: Relevance
“…Proteobacteria and Firmicutes were the dominant phyla, with Escherichia–Shigella, Fusobacterium , and Enterococcus the major genera. Even though the interpretation of 16S sequence data for assigning a definitive bacterial species was limited ( Church et al., 2020 ), E. coli was found to be the most abundant species, which was consistent with traditional culture data. LEfSe revealed that no taxon from the biliary microbiota was found to be differentially more abundant as compared to the duodenal microbiota, suggesting that bile shared similar bacterial communities with duodenal juice in patients with choledocholithiasis.…”
Section: Discussionsupporting
confidence: 70%
“…Proteobacteria and Firmicutes were the dominant phyla, with Escherichia–Shigella, Fusobacterium , and Enterococcus the major genera. Even though the interpretation of 16S sequence data for assigning a definitive bacterial species was limited ( Church et al., 2020 ), E. coli was found to be the most abundant species, which was consistent with traditional culture data. LEfSe revealed that no taxon from the biliary microbiota was found to be differentially more abundant as compared to the duodenal microbiota, suggesting that bile shared similar bacterial communities with duodenal juice in patients with choledocholithiasis.…”
Section: Discussionsupporting
confidence: 70%
“…Nucleic acid sequence of the bacterial 16S rRNA gene has been used for several decades to identify routine identification of bacterial pathogens [18].The 16S rRNA gene sequencing technology was applied to detect the V3-V4 region of bacterial species in twenty-four stool samples from five groups (PBS, CT26, CT26-L, CT26-M, CT26-H) and was entrusted to Personal Bio company.…”
Section: Gm Analysismentioning
confidence: 99%
“…Of note, Sabat et al reported improved bacterial species identification via targeted NGS of both 16S and 23S rRNA sequences [43], where the sequencing was performed on DNA extracted directly from urine and orthopedic samples, in addition to those from blood culture bottles. A recent review by Church et al provides a comprehensive summary on the performance of the 16S rRNA gene sequence for bacterial identification [90].…”
Section: Low Taxonomical Resolution In 16sngs Sequencing Readsmentioning
confidence: 99%